Driving assessment and rehabilitation using a driving simulator in individuals with traumatic brain injury: A scoping review. - Imhoff, Sarah; Lavalliére, Martin; Teasdale, Normand; Fait, Philippe (NeuroRehabilitation, 2016)
BACKGROUND: Due to the heterogeneity of the lesion following a traumatic brain injury (TBI) and the complexity of the driving task, driving assessment and rehabilitation in TBI individuals is challenging. Conventional driving assessment (on-road and in-clinic evaluations) has failed demonstrating effectiveness to assess fitness to drive in TBI individuals. OBJECTIVE: We aimed to determine if driving simulators represent an interesting opportunity in assessing and rehabilitating driving skills in TBI individuals. METHODS: We searched PubMed, CINAHL and Cochrane library databases between 27-02-2014 and 08-04-2014 for articles published since 2000 with the contents of simulator driving assessment and rehabilitation. RESULTS: Out of 488, eight articles with the subject of simulator driving assessment and two with the subject of simulator driving rehabilitation in individuals with TBI were reviewed. CONCLUSIONS: Driving simulators represent a promising avenue for the assessment and rehabilitation of driving skills in TBI individuals as it allows control of stimuli in a safe, challenging and ecologically valid environment and offer the opportunity to measure and record driving performance. Additional studies, however, are needed to document strengths and limitations of this method.